Physical Activity Throughout the Adult Life Span and Domain-Specific Cognitive Function in Old Age: A Systematic Review of Cross-Sectional and Longitudinal Data - Engeroff, Tobias; Ingmann, Tobias; Banzer, Winfried (Sports medicine (Auckland), 2018)
Background A growing body of literature suggests that physical activity might alleviate the age-related neurodegeneration and decline of cognitive function. However, most of this evidence is based on data investigating the association of exercise interventions or current physical activity behavior with cognitive function in elderly subjects. Objective We performed a systematic review and hypothesize that physical activity during the adult life span is connected with maintained domain-specific cognitive functions during late adulthood defined as age 60+ years. Methods We performed a systematic literature search up to November 2017 in PubMed, Web of Science, and Google Scholar without language limitations for studies analyzing the association of leisure physical activity during the adult life span (age 18+ years) and domain-specific cognitive functions in older adults (age 60+ years). Results The literature review yielded 14,294 articles and after applying inclusion and exclusion criteria, nine cross-sectional and 14 longitudinal studies were included. Moderate- and vigorous-intensity leisure physical activity was associated with global cognitive function and specific cognitive domains including executive functions and memory but not attention or working memory. Most studies assessed mid- to late-adulthood physical activity, thus information concerning the influence of young adult life-span physical activity is currently lacking. Conclusions Observational evidence that moderate- and vigorous-intensity leisure physical activity is beneficially associated with maintained cognitive functions during old age is accumulating. Further studies are necessary to confirm a causal link by assessing objective physical activity data and the decline of cognitive functions at multiple time points during old age.